Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Sales Marketing Hotel Berbintang di Kota Padang - Jennyfer Jennyfer; Hijriyantomi Suyuthie (Nawasena: Jurnal Ilmiah Pariwisata, 2025)
This study examines the impact of compensation and work environment on the performance of Sales Marketing in star-rated hotels in Padang City. Using a quantitative method with a causal research design, this study involved 30 respondents selected through purposive sampling. Data collection was conducted using a questionnaire designed based on a Likert scale as the research instrument. The collected data were analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS). The hypothesis testing results indicate that compensation has a positive and significant effect on performance, with a t-statistic value (2.660) greater than the t-table (1.66) and a p-value of 0.008 less than 0.05. The work environment also has a positive and significant effect on performance, with a t-statistic value (2.975) greater than the t-table (1.66) and a p-value of 0.003 less than 0.05.